Allele frequency in thyroid cancer: mechanisms, challenges, and applications in cancer therapy - Jiayu Huang; Jiazhi Wang; Guangzhi Wang; Yongfu Zhao (Thyroid Research)
Abstract Allele Frequency (AF) is the percentage of sequence reads with a specific mutation relative to the read depth at that locus, reflecting the proportion of gene mutation. This review explores the AF characteristics of different mutations in thyroid cancer, investigating their connection with tumor features and clinical characteristics. BRAF mutation AF is associated with tumour malignancy and prognosis, exhibiting a relatively low peak value. TERT mutations in AF are associated with invasive characteristics, and the combination between BRAF and TERT mutations AF improved the diagnostic value in identifying patients' risk of recurrence and tumour malignancy. RET mutation is frequently observed in medullary carcinoma, and RET mutation AF is associated with partial tumour characteristics. RAS mutation is prevalent in follicular tumors, but the association between RAS mutation AF and tumour characteristics is relatively weak. TP53 mutation is more frequently occurred in poorly differentiated and anaplastic carcinoma, and its AF might be associated with the dedifferentiation process. We also concentrated on the mutually exclusive and synergistic effect between different mutations. The mutation rate of TERT increases with the elevation of BRAF mutation AF. Finally, the detection and assessment of AF by NGS in clinical practice helps to provide a reference for individualised targeted therapy plans.